Ectoparasites Identification on Spiny Lobster (Panulirus homarus) Cultivated Controlled Tanks and Floating Net Cages (KJA) at the Lampung Marine Aquaculture Center (BBPBL) : Identifikasi Ektoparasit Lobster Pasir (Panulirus homarus) pada Bak Terkendali dan Keramba Jaring Apung (KJA) di Balai Besar Perikanan Budidaya Laut (BBPBL) Lampung - Fatimatuzzahra, Izza; Istiadi, Khaerunissa Anbar; Garbono, Andrian (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Ectoparasites can infect aquatic biota, including spiny lobster (Panulirus homarus), which causes failure of spiny lobster cultivation, such as death, bacterial infection, and decreased cultivation quality. One of the failures of spiny lobster cultivation is often caused by ectoparasite disorders. Environmental conditions influence the growth and distribution of ectoparasites. This study aims to identify the types of ectoparasites and factors that influence the presence of ectoparasites in spiny lobsters and determine the intensity and dominance of spiny lobster ectoparasites. The study was conducted in floating net cages (KJA). It controlled Lampung Marine Aquaculture Center (BBPBL) tanks by purposive random sampling with 18 spiny lobsters, each taken from KJA and controlled tanks. The stages of the study included taking mucus samples on the tail and swimming legs (pleopods), microscopic examination of ectoparasites, calculating the intensity and dominance of ectoparasites, and measuring water quality parameters. The study results obtained three ectoparasites infecting the Spiny lobster, including the Protozoa phylum and the Ciliata class: Vorticella sp., Zoothamnium sp., and Epistylis sp. The intensity of Vorticella sp. ectoparasite attacks was 11.5/lobster. The most dominant ectoparasite was the Vorticella sp. type at 53.90%. The difference in the number of ectoparasites in controlled tanks and floating net cages was due to differences in temperature, size of the cultivation container, and depth, which affected water quality.